The Housing Situation and Needs of Immigrants in the Canadian Metropolitan Areas of Toronto, Vancouver and Montreal - Li, Sibei (Université d'Ottawa | University of Ottawa, 2017)
Access to adequate, suitable and affordable housing is an essential step in immigrant’s integration. With data from the Public Use Individual Microdata File of the 2011 National Household Survey, I examine the relationship between six selected housing condition indicators and the socio-economic characteristics of households, comparing the immigrants to the Canadian-born in Toronto, Montreal and Vancouver. The housing condition indicators that are selected include whether the household owns or rents, whether the household pays more than 30% of its monthly income on rent, whether the household uses debt or mortgage to finance a house, whether the household pays more than 30% of its monthly income on mortgage, whether the household lives in a house that needs to be repaired, and whether the household lives in suitable housing given its size. The related characteristics of households include the places of birth of the immigrants, the census metropolitan area where people live, the education level, age, gender, household size, employment status, years since immigration, and the presence of kids in a census family. In general, immigrants from Hong Kong and China are the most likely to have adequate and suitable housing conditions and immigrants from Latin America and Africa are the least likely to be in such situation.